Inhibition of 5-lipoxygenase by zileuton in a rat model of myocardial infarction - (:unkn) unknown (My University, 2017)
0

Objective: The goal of the present study was to investigate the effects of 5-lipoxygenase (5-LOX) inhibition, alone and with cyclooxygenase (COX) inhibitors, on inflammatory parameters and apoptosis in ischemia/reperfusion (I/R)-induced myocardial damage in rats. For this purpose, zileuton, a selective and potent inhibitor of 5-LOX, resulting in suppression leukotriene production, was used.Methods: Male Wistar rats (200-250 g; n=12 per group) were used in the study. I/R was performed by occluding the left coronary artery for 30 minutes and 2 hours of reperfusion of the heart. Experimental groups were I/R group, sham I/R group, zileuton (5 mg/kg orally, twice daily)+I/R group, zileuton+indomethacin (5 mg/kg intraperitoneally)+I/R group, zileuton+ketorolac (10 mg/kg subcutaneously)+I/R group, and zileuton+nimesulide (5 mg/kg subcutaneously)+I/R group. Following I/R, blood samples were collected to measure tumor necrosis factor alpha (TNF-α), and left ventricles were excised for evaluation of microscopic damage; malondialdehyde (MDA), glutathione, nuclear factor (NF)-κB assays; and evaluation of apoptosis.Results: Left ventricle MDA in I/R group was higher compared to sham group; however, it did not show significant change with zileuton. Although tissue injury in I/R group was less severe in all treatment groups, it was not statistically significant. NF-κB H-score and apoptotic index, which were higher in I/R group compared to sham I/R, were decreased with application of zileuton (H-score: p<0.01; apoptotic index: p<0.001). Zileuton had no significant effect on increased serum TNF-α levels in I/R group.Conclusion: 5-LOX inhibition in rat myocardial infarction model attenuated increased left ventricle NF-κB expression and apoptosis and these actions were not modulated by COX inhibitors
Keywords: Kalp ve Kalp Damar Sistemi